Silicagel-supported H6P2W18O62.24H2O: A reusable catalyst to prepare diphenylmethyl (DPM) ethers - Romanelli, Gustavo Pablo (2007)
In this work, we report an efficient and facile preparation of diphenylmethylethers (benzydryl ethers, DPM-ethers) from benzhydrol and alcohols or phenols. Wells-Dawson heteropolyacid (H6P2W 18O62.24H2O), bulk or supported on silica showed catalytic activity for DPM-ethers preparation in toluene, at 60-80°C, in 0.5-1.5h. In these conditions twelve diphenylmethylethers of alcohols and phenol were obtained which excellent yields (78-96%). The heterogeneous reaction conditions provided a very simple, environmentally friendly, clean, economical and selective protocol, for the preparation of unsymmetrical ethers. The catalyst is easily recycled and reused without loss of the catalytic activity.